The Key Role of Brain-Derived Neurotrophic Factor (BDNF) in Pathophysiology of Glaucoma and Its Therapeutic Potential: Brain-Derived Neurotrophic Factor (BDNF) in Pathophysiology of Glaucoma - Durrani, Muhammad Usman; Usman, Anum; Noureen, Fakhra; Munim, Abdul; Abbas, Sohaib; Bilal Ahmed, Zain ul Abden; Khaliq, Muhammad Haseeb (Pakistan Journal of Health Sciences, 2024)
Glaucoma, a leading cause of irreversible blindness, is increasingly recognized as a neurodegenerative disease affecting broader neuro-ophthalmic pathways. Brain-derived neurotrophic Factor is a crucial neurotrophin, that supports the growth, maintenance, and survival of neurons and has been implicated in glaucomatous damage where its levels are diminished. Objectives: To focus on the role of Brain-Derived Neurotrophic Factor in the pathophysiology of glaucoma and its therapeutic potential by enhancing the survival of retinal ganglion cells. Methods: The studies in this review are taken from well-known public libraries for scientific research such as PubMed (60%), Science Direct (25%) and Springer Link (15%), in line with PRISMA guidelines. Various works conducted over the past decade from different parts of the world, including North America, Europe, and Asia, have provided evidence that the augmentation of Brain-Derived Neurotrophic Factor signalling may be a very effective approach to managing or halting the progression of glaucomatous optic neuropathy through neuroprotection and improving retinal ganglion cells survival. Results: Studies in both animals and humans indicate that Brain-Derived Neurotrophic Factor and its downstream signals promote the survival of retinal ganglion cells and decrease the extent of apoptotic cell death, oxidative stress, and inflammation in glaucoma. Moreover, enhancements of Brain-Derived Neurotrophic Factor neuroprotective effects are supported by factors such as Nerve growth factor and Brain-Derived Neurotrophic Factor. Conclusion: It was concluded that Brain-derived neurotrophic Factor has the potential to be used as a diagnostic marker for Glaucoma as well as it could be evaluated for its therapeutic potential against the disease.